Edukasi Kesehatan Tentang Hipertensi Pada Kehamilan - Sri Rahayu; Faizah Betty Rahayuningsih; Wita Oktaviana; Jiheny Siska Pratiwi; Thia Wulan Dinasti; Adelia Nur Aziza (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Hypertension in pregnancy is still one of the causes of increased morbidity and mortality rates in pregnant women. Meanwhile, there are still many pregnant women who do not fully understand hypertension in pregnancy. RSUD dr. Soeratno Gemolong is one of the Sragen regional government hospitals which has almost the same problem. The solution that can be taken is by carrying out promotive and preventive actions for pregnant women. One way is by conducting health education, which aims to increase pregnant women's knowledge about hypertension during pregnancy. The method used is through health education. There were 24 participants involved in the pre-test, and 27 people in the post-test. As a result of this community service, it was found that there was an increase in knowledge about hypertension in pregnant women from 70.83% to 85.16% after health education was carried out. Thus, it can be concluded that health education has an important role to increase pregnant women's knowledge about hypertension in pregnancy.